فعالية وسائط الباوربوينت (powerpoint) المعتمدة على تقنيّة التقليد الحركي في تعزيز مفردات اللغة العربية لدى طلاب المدرسة المتوسطة الحكومية الأولى في تولونغاغونغ - Zuyyina Ilmy Azizah; Munirul Abidin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research investigates how effective the use of instructional media based on PowerPoint (PPT), when integrated with mime techniques, is in improving students' mastery of vocabulary. The study is driven by the recurring problem of students having a limited range of vocabulary, which frequently becomes an obstacle in the process of acquiring language skills. A quantitative research method with a quasi-experimental framework was employed, involving two separate groups of participants: an experimental class exposed to mime-supported PPT instruction, and a control class taught using traditional methods without the aid of visual media. To measure learning outcomes, both pre-tests and post-tests were administered, and the data obtained were examined using an independent sample t-test. The experimental group was taught using the تقنيّة التقليد الحركي technique enhanced by multimedia presentation, while the control group relied solely on conventional instruction. The analysis indicated a notable he findings revealed a notable enhancement in the vocabulary skills of the experimental group, demonstrated by an increase in their average post-test scores. Scores increasing from 47.59 to 77.59. In contrast, the control group showed a more moderate gain, from 48.33 to 63.67. These results underscore the value of integrating PowerPoint into the تقنيّة التقليد الحركي approach, which appears to significantly reinforce vocabulary retention and engagement. Consequently, this study advocates for more creative and interactive strategies in Arabic language instruction, especially in addressing persistent vocabulary learning challenges.